The Impact of Islamic Integrative Math Problems with Science, Technology, Engineering, and Mathematics (STEM) Education Framework to Improve Critical Thinking Skills - Nu'man, Mulin (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
Daily, no problem can be solved by involving only one scientific discipline. Students must be trained with integrative problems involving other disciplines. STEM education is one educational framework that allows students to be engaged in integrative problems. This study aims to determine the effectiveness of Islamic integrative mathematics problems with STEM education in improving critical thinking skills. Effectiveness is also seen based on critical thinking skills, including understanding problems, identifying information, validating arguments, drafting conclusions, and evaluating. The research method used is a quasi-experiment with a pretest and posttest control group design. The research population is 8th-grade MTs/Islamic Junior High School students in Purbalingga, with a sample of 138 students from two Islamic junior high schools. Critical thinking skills data was obtained from a critical thinking skills test representing each aspect of critical thinking. The data analysis used was the t-test and the Mann-Whitney U test with the help of SPSS. The study results show that learning integrative math problems with STEM education effectively improves overall critical thinking skills and the aspects of argument validation and evaluation. Meanwhile, in terms of understanding problems, identifying information, and concluding, Islamic integrative mathematics problems with STEM education are not effective. The finding implies that learning mathematics is more meaningful if it is directly related to its application in various disciplines, in this case, STEM and Islamic disciplines. Integrating mathematics with various disciplines in the form of integrative math problems can develop students' critical thinking skills well.